Non-thermal plasma activated water is an effective nitrogen fertilizer alternative for Arabidopsis thaliana - Jonathan Kizer; Conner Robinson; Ta’Kia Lucas; Steven Shannon; Ricardo Hernández; Katharina Stapelmann; Marcela Rojas-Pierce (PLoS ONE, 2025)
Nitrogen (N) fixation with non-thermal plasmas has been proposed as a sustainable alternative to meet growing N fertilizer demands for agriculture. This technology generates Plasma Activated Water (PAW) with a range of chemical compositions, including different concentrations of nitrate (NO₃⁻) and hydrogen peroxide (H 2 O 2 ), among other compounds. Potential use of PAW as an effective crop fertilizer necessitates a robust understanding of the underlying biology of the plant, which is not yet available. The lack of a unified standard in PAW production and the varying chemical make-up that results from different devices and protocols hampers comparative studies and adoption of this technology. The objective of this study was to compare the efficacy of two PAW solutions with differing concentrations of H 2 O 2 produced from a Radio Frequency (RF) glow discharge plasma source. The effect of these solutions on plant growth, ROS accumulation, gene expression and heat stress response were compared to N-equivalent controls in the model plant Arabidopsis to assess their potential as an alternative N fertilizer. While PAW solutions lacking detectable H 2 O 2 enhanced seedling growth, those containing approximately 0.3 µM of H 2 O 2 did not. ROS accumulation in root tissues was similar between PAW and chemically equivalent solutions, suggesting H 2 O 2 is the primary ROS present in the PAW at the time of treatment. Gene expression studies showed induction of genes involved in N uptake and assimilation in PAW-treated seedlings. Pre-treatment of seedlings with PAW solutions containing H 2 O 2 improved root growth under heat stress which indicates that this treatment may induce plant stress response pathways. Finally, mature plants showed similar growth when fertilized with PAW lacking H 2 O 2 or NO 3 - control regimes for over 5 weeks indicating equivalency in chemical composition, plant nutrient uptake and utilization. Overall, these results demonstrate that PAW is an effective alternative to NO 3 - fertilizers for plant cultivation but the levels of H 2 O 2 need to be carefully controlled.